2022
DOI: 10.1038/s41598-022-22699-8
|View full text |Cite
|
Sign up to set email alerts
|

Presence of entry receptors and viral markers suggest a low level of placental replication of hepatitis B virus in a proportion of pregnant women infected with chronic hepatitis B

Abstract: The transplacental route of vertical transmission of Hepatitis B Virus (HBV) has been known for over a decade. Here we present evidence which suggest HBV can replicate in placenta. Forty-one HBsAg positive and 10 control pregnant women were enrolled in the study after obtaining informed consent. HBV positives were further divided in the High Viral Load (HVL) Group and Low Viral Load (LVL) Group according to INASL guidelines 2018. The Presence of the HBV DNA and expression of NTCP in the placenta was analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Several routes of the vertical transmission of pathogens across the maternal–fetal interface are known to occur, including direct transplacental transmission, placental disruption, fetal–maternal hemorrhage, transmission across fetal membranes, and ascending infections [ 38 , 39 ]. The presence of viral components in the placenta may be due to the translocation of viral components from peripheral blood or viral replication in the placenta [ 40 ]. We previously showed that BPVs have the potential to replicate in the placenta as we detected BPV L1 expression in the binucleate trophoblast cells of the placenta from pregnant cows [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several routes of the vertical transmission of pathogens across the maternal–fetal interface are known to occur, including direct transplacental transmission, placental disruption, fetal–maternal hemorrhage, transmission across fetal membranes, and ascending infections [ 38 , 39 ]. The presence of viral components in the placenta may be due to the translocation of viral components from peripheral blood or viral replication in the placenta [ 40 ]. We previously showed that BPVs have the potential to replicate in the placenta as we detected BPV L1 expression in the binucleate trophoblast cells of the placenta from pregnant cows [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate trophoblastic invasion and immune response could promote dysfunction of the placenta and alter the blood flow to the fetus, 22 while interruption of blood supply to fetus is associated with ACC. As HBV biomarkers could be detected in the placenta, 23 , 24 another possible pathogenic mechanism could involve maternally generated antibodies to HBsAg, PreS1, or PreS2, and the corresponding antigens that form circulating complexes. These complexes could deposit in the capillaries of the placenta and cause thrombotic events that might disrupt skin development in the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Garima et al. ( 57 ) also observed that even at relatively low levels, receptors and HBV markers could replicate in the placenta. As the placenta developed, trophoblast cells differentiated and fused into multinucleated cells that formed the syncytiotrophoblast, and the maturity of the placenta and specific maternal antibodies, such as maternal immunoglobulin G (IgG), had the ability to reduce the risk of HBV transmission ( 55 ).…”
Section: T Cells and Hbv Infectionmentioning
confidence: 98%